Inovasi dan Pengembangan Kurikulum dalam Berbagai Konteks Pendidikan - Azizah Muslikhatun; Windah Lestari; Tutik Poncowati; Bebet Adi Wibawa; Ngurah Ayu Nyoman Murniati (JANACITTA, 2025)
Abstract This study aims to examine various forms of curriculum innovation and development in different educational contexts in Indonesia, including early childhood education, basic education, Islamic schools, and inclusive education. The research employed a literature study by analyzing nationally accredited journal articles published between 2018 and 2024. Article selection was based on keywords such as curriculum innovation, Merdeka Curriculum, Islamic education, inclusive education, and early childhood education. The findings indicate that curriculum innovation in Indonesia is highly contextual. In inclusive education, innovations include the application of the 4D model and curriculum modification through cooperative learning for students with special needs. In early childhood education, flexible play-based curriculum is the main innovation. In basic education, innovation appears in the implementation of the Merdeka Curriculum and the integration of national curriculum with Islamic values through KPPM and tahfidz programs. In Madrasah Tsanawiyah, curriculum innovation is realized through anti-radicalism approaches that promote religious moderation. In conclusion, the identified innovations focus on curriculum flexibility, integration of local and religious values, character development, and inclusive education access. However, challenges such as limited resources, teacher readiness, and policy–practice gaps must be addressed through sustainable, collaborative, and contextual implementation strategies.  Abstrak  Penelitian ini bertujuan mengkaji bentuk-bentuk inovasi dan pengembangan kurikulum dalam berbagai konteks pendidikan di Indonesia, mulai dari PAUD, pendidikan dasar, madrasah, hingga pendidikan inklusif. Metode yang digunakan adalah studi literatur dengan menganalisis artikel dari jurnal nasional terakreditasi yang diterbitkan pada periode 2018–2024. Pemilihan artikel didasarkan pada kata kunci inovasi kurikulum, Kurikulum Merdeka, pendidikan Islam, pendidikan inklusif, dan pendidikan anak usia dini. Hasil telaah menunjukkan bahwa inovasi kurikulum di Indonesia bersifat kontekstual. Pada pendidikan inklusif, inovasi berupa penerapan model 4D dan modifikasi kurikulum berbasis cooperative learning untuk anak berkebutuhan khusus. Pada PAUD, fleksibilitas kurikulum berbasis bermain menjadi inovasi utama. Pada sekolah dasar, inovasi tampak pada penerapan Kurikulum Merdeka serta integrasi kurikulum nasional dengan nilai-nilai keislaman melalui KPPM dan program tahfidz. Di Madrasah Tsanawiyah, inovasi dilakukan melalui kurikulum anti-radikalisme yang menanamkan moderasi beragama. Kesimpulannya, inovasi kurikulum yang ditemukan berfokus pada fleksibilitas pembelajaran, integrasi nilai lokal dan religius, penguatan karakter, serta akses pendidikan inklusif. Namun, tantangan berupa keterbatasan sumber daya, kesiapan guru, dan kesenjangan kebijakan masih perlu diatasi dengan strategi implementasi yang berkelanjutan, kolaboratif, dan kontekstual.